Structural elucidation of galactomannan from ‘Petai Belalang’(Leucaena leucocephala) and its modified analogue - Shirajuddin, Shazlinda; Kamarun, Dzaraini; Thomas, Sabu (International Journal of Engineering and Technology, 2018)
Galactomannan (GM) is a biomoleculer polymer present as a storage carbohydrate in endosperm of many leguminous plant and fungal cell wall. Commercial GMs were obtained from plants such as guar gum (Cyamoposis tetragonolobus), locust beans (Ceratonia siliqua) and tara gum (Caesalpinia spinosa). In this project GM was extracted from seeds of a local plant ‘petai belalang’ scientifically known as Leucaena leucocephala. The GM was further conjugated with acryloyl groups for further crosslinking reactions. We report here the structural properties of the modified analogue of GM based on several spectroscopic techniques such as FTIR, NMR and XRD. The morphology of the galactomannan analogue (aGM) was identified from SEM images at several magnifications. We also included discussions on comparisons of the aGM from its parent structure. GM was successfully conjugated with the acryloyl group as verified by the presence of vinyl stretching bands and vinyl protons in the FTIR and H1 NMR spectrum of aGM respectively. This is supported with SEM images that show distribution of granules along the aGM surfaces as compared to a smooth surface of its parent compound. The successfulness of the conjugation process was further verified from data obtained from thermogravimetric analysis (TGA).